Determination of Glucose Solution Concentration Using Arduino-Based System - Herbert Innah; Maniur Arianto Siahaan (Science Journal Get Press, 2025)
Glucose is one of the most important biomolecules, playing a critical role in biological systems, food products, and clinical diagnostics. Conventional methods for glucose concentration measurement, such as spectrophotometry and enzymatic assays, although accurate, are often costly, time-consuming, and require skilled personnel. This study presents the development of a low-cost Arduino-based optical detection system for measuring glucose concentration using RGB LEDs as light sources and a photodiode sensor as the detector. The Arduino microcontroller processes voltage signals corresponding to light intensity and calculates absorbance values based on Beer-Lambert’s law. Calibration was performed using glucose solutions of varying concentrations, and the results indicated that the red LED source provided the most accurate and stable absorbance readings, with an average relative error below 5%. The proposed system offers an affordable, portable, and reliable alternative to conventional spectrophotometers, making it suitable for educational laboratories, small-scale food industries, and preliminary biomedical testing. Its implementation demonstrates the potential of microcontroller-based systems in enhancing accessibility to analytical tools in resource-limited environments.